2007
DOI: 10.1111/j.1600-0714.2007.00571.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of hypoxia‐inducible factor‐1α is significantly associated with the progression and prognosis of oral squamous cell carcinomas in Taiwan

Abstract: We conclude that the expression of HIF-1 alpha is an early event in oral carcinogenesis. The nuclear HIF-1 alpha LI in OSCC samples can predict the progression of OSCCs and the survival of OSCC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 34 publications
(75 reference statements)
5
58
2
Order By: Relevance
“…Recent research indicates that the tumor microenvironment such as hypoxia might play an important role in the uptake of FDG (7) involving a variety of mechanisms. Hypoxia is also associated with resistance to chemotherapeutic drugs and poor prognosis (12)(13)(14). Thus, the present study investigated the correlations between the SUVmax of FDG-PET, the histological effect following neoadjuvant chemoradiotherapy, and expression of the hypoxia-related marker HIF-1· which upregulates GLUT-1 and VEGF in OSCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research indicates that the tumor microenvironment such as hypoxia might play an important role in the uptake of FDG (7) involving a variety of mechanisms. Hypoxia is also associated with resistance to chemotherapeutic drugs and poor prognosis (12)(13)(14). Thus, the present study investigated the correlations between the SUVmax of FDG-PET, the histological effect following neoadjuvant chemoradiotherapy, and expression of the hypoxia-related marker HIF-1· which upregulates GLUT-1 and VEGF in OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…It has been noted that the tumor microenvironment of many malignancies contains a hypoxic condition, a condition associated with resistance to anticancer agents and poor prognosis (12)(13)(14). Hypoxia-inducible factor-1· (HIF-1·) was found to be upregulated in a broad range of tumors and is involved in angiogenesis, invasion and altered glucose metabolism (14,15). Therefore, we focused on the hypoxic condition related to malignant potential and glucose metabolism in malignant tumors.…”
Section: Introductionmentioning
confidence: 99%
“…However, clinicopathological variables and tumour-specific molecular markers that can identify patients with the highest risk of local recurrence have yet to be defined. 16,[18][19][20][21][22][23][42][43][44][45][46][47][48][49] Vimentin, a mesenchymal cell marker, associates with components of the cytoskeleton and membrane adhesions. Studies of human epithelial carcinomas, such as breast cancer, hepatocellular carcinoma, colon carcinoma, and prostatic adenocarcinoma, have shown that vimentin expression can be correlated with tumour invasion and a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…HIF-1 is recognized as a key player in the transcriptional response to hypoxia (11)(12)(13). HIF-1 is a heterodimer composed of an a-subunit (HIF-1a) and a b-subunit (HIF-1b), and its activity is mainly dependent on the stability and modification of HIF-1a, the expression of which is highly regulated (10,12).…”
mentioning
confidence: 99%